THE MAN WHO TEACHES ENTREPRENEURS TO MIGRATE STRATEGICALLY AND THRIVE IN THE UNITED STATES (International Seven Journal of Multidisciplinary, 2021)
Migration can be a powerful driver of economic opportunity, but immigrant entrepreneurs often face significant barriers when establishing businesses in the United States. This article examines the work of Joe Douglas, an American business strategist who mentors immigrant entrepreneurs through strategic migration planning, targeted training, and community-based support initiatives. Douglas’s programs address legal, cultural, and financial obstacles by offering practical tools such as financial literacy workshops, cultural adaptation training, and access to alternative funding sources. His emphasis on pre-migration preparation and post-arrival integration reflects best practices supported by academic research. Through digital platforms and collaborative events, Douglas has created a replicable model that fosters entrepreneurial success and enhances economic inclusion. His work contributes to broader debates on migration policy and underscores the potential of grassroots mentorship to promote sustainable immigrant entrepreneurship in the U.S. context.